2008
DOI: 10.1590/s1415-47572008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and hypothalamic gene expression in early- and late-maturing Bos indicus Nellore heifers

Abstract: We investigated wether early-maturing or late-maturing Bos indicus Nellore heifers produced more leptin mRNA in adipose tissues and altered expression of hypothalamic genes related to leptin signaling. Six prepubertal and six pubertal heifers aged about 34 months and weighing 280 kg to 300 kg each were selected from a population of 100 Nellore heifers. Real-time PCR was used to quantify the expression of the leptin gene (LEP) in adipose tissues and the long isoform of the leptin receptor gene (Ob-Rb), the NK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
4
0
4
Order By: Relevance
“…However, the authors reported that early-maturing heifers had reduced expression of two hypothalamic NPY receptors, NPY1R and NPY4R. The results of the present study, together with the results of Vaiciunas et al (2008), support the hypothesis that signaling through the NPY receptors modulates both nutrition and genetics effects on the attainment of puberty in Nellore heifers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the authors reported that early-maturing heifers had reduced expression of two hypothalamic NPY receptors, NPY1R and NPY4R. The results of the present study, together with the results of Vaiciunas et al (2008), support the hypothesis that signaling through the NPY receptors modulates both nutrition and genetics effects on the attainment of puberty in Nellore heifers.…”
Section: Discussionsupporting
confidence: 82%
“…As observed in this study, the reduction of NPY1R expression by high energy intake suggests that it would make the hypothalamus less sensitive to NPY inhibition, enabling earlier onset of puberty. The role of NPY and its receptors in modulating puberty attainment of early-and late-maturing heifers was analyzed by Vaiciunas et al (2008), who reported that NPY expression was not significantly altered in early-maturing heifers. However, the authors reported that early-maturing heifers had reduced expression of two hypothalamic NPY receptors, NPY1R and NPY4R.…”
Section: Discussionmentioning
confidence: 99%
“…The late onset to puberty, which is generally observed in B. indicus when compared with B. taurus, directly affects profit in the cattle industry since it can postpone the start of the reproductive life of a cow for one year. Hence, the development of tools for the identification of more efficient cattle in this regard is of great commercial interest (Vaiciunas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was reported by Vaiciunas et al (2008), which verified that precocious heifers had lower expression of hypothalamic NPY receptors.…”
Section: Introductionsupporting
confidence: 86%